Opportunities for waste valorisation in the food industry – A case study with four UK food manufacturers. (20th February 2019) - Garcia-Garcia, Guillermo; Stone, Jamie; Rahimifard, Shahin
Abstract: Food manufacturing is comprised of a number of complex processes which generate vast amounts of food waste. Frequently, strategies for dealing with these materials are rudimentary and provide a low economic and environmental value, for instance animal feeding, anaerobic digestion, composting, incineration, landspreading and landfilling. However, food wastes contain numerous chemicals with a wide range of potential commercial applications, which makes these materials suitable feedstocks for valorisation. This paper applies a Waste Flow Modelling methodology to achieve two aims: to provide valuable food manufacturing and waste data in order to better understand current food manufacturing activities, and to analyse existing food waste management practices to lay the foundation for the implementation of alternative food waste valorisation solutions. Four UK industrial companies have been selected and assessed to represent four different food sectors where food waste valorisation could provide an economic and/or environmental advantage: a fruits supplier, a brewery, a potato supplier and a producer of peas. The production line of each of these four businesses is defined and characterised, which allows the identification of food wastes generated. Next, food wastes are categorised and quantified, and their patterns of generation and current waste management practices are described. Sankey diagrams and performance indicators are used to assess the efficiency of processes, combination of processes and the complete production line in terms of food waste generation. Finally, the results are analysed and used to obtain the main conclusions and provide recommendations for an improved food waste management system, with a focus on valorisation opportunities. Graphical abstract: Highlights: Vast quantities of food wastes are generated by UK food manufacturers. Frequently, food wastes are considered low-valuable materials. There are opportunities to valorise food waste from the food industry. A novel systematic methodology is used to identify and explore such opportunities. Valorisation should improve the sustainability performance of food waste management.